An evaluation of the impact of PROGRESA on preschool child height - Behrman, Jere R.; Hoddinott, John F. (International Food Policy Research Institute, 2001)
One of the major components of the PROGRESA program has been directed toward improving the nutritional status of small children in poor rural communities in Mexico. Results suggest that PROGRESA may be having fairly substantial effects on lifetime productivities and earnings of currently small children in poor households.